Coastal urbanization-related stressors affect fish herbivory in the Spermonde Archipelago, Indonesia - Estradivari; Andi M. A. Pratama; Gunawan Syafruddin; Puspita L. Kanna; Marleen Stuhr; Andrew F. Torres; Munawwarah; Dino A. Ramos; Rohani Ambo-Rappe; Sonia Bejarano; Oscar Puebla; Christian Wild; et al. (Frontiers in Marine Science, 2025)
Coastal urbanization has significantly degraded coral reef habitats worldwide, often driving shifts from coral to algal dominance. Quantifying fish herbivory, a key ecological process mitigating such transitions, is essential for understanding reef health, functioning, and resilience. This study examined herbivory rates (bites multiplied by fish biomass) across five fish functional groups (detritivores, croppers, browsers, scrapers, and excavators) in relation to coral reef conditions along a gradient of urban influence in the Spermonde Archipelago, Indonesia. Herbivory rates generally increased from inshore to offshore sites, with notable differences among functional groups. Cropper and scraper herbivory varied significantly across sites, while detritivore and excavator rates were consistent. Browser herbivory was only observed at the most offshore site, highlighting potential vulnerability of the browsing function near urban centers. Environmental factors influenced herbivory rates in distinct ways. Detritivore herbivory was higher on reefs with lower rugosity, likely due to increased sediment accumulation on flatter substrates. Herbivory rates of all herbivorous fish, and of croppers, scrapers and excavators individually, were strongly correlated with the organic matter content of turf algae sediments, underscoring the importance of food quality in shaping herbivory dynamics. Experimental manipulation of turf algae sediments (clearing vs . control) did not affect herbivory rates, suggesting that the effects of sediment accumulation are not the main driver of herbivory patterns at the studied sites. Preserving functional and taxonomic diversity among herbivorous fish is critical for maintaining reef resilience amidst increasing urbanization and local stressors.